SC53 Using simulation-based education to support return to work in paediatrics. (3rd November 2019) - Patel, Ashish; Holt, Ashley; Copeman, Annabel; Belfitt, Alison
Abstract : Background: Time out of training is common for paediatric trainees. When returning back to work, trainees often feel anxious and lack confidence. As well as feeling de-skilled, there is also the emotional aspects of dealing with sick children, particularly following maternity leave. Given the recent Bawa-Garba case, anxiety amongst paediatric trainees returning to work is even greater. The Royal College of Paediatrics and Child Health (RCPCH) indicates that returning paediatricians should be supported with a formal return to work programme. Thus, a Paediatric Return to Work Simulation Course was developed within our region to facilitate this requirement. Summary of Education Programme: All out of programme trainees are invited to attend a one-day course of high fidelity simulation, at the simulation centre at The Royal Wolverhampton NHS Trust. The course runs four times a year and fully funded by Health Education England. The scenarios are mapped to the RCPCH Curriculum, covering key aspects and skills of paediatric training including safeguarding, emergency management of acutely unwell children, leadership, communication and human factors. Summary of results: To date a total of 68 candidates have attended our return to work simulation course. Some trainees have attended more than one course having had more than one break in training. The course was evaluated using a questionnaire, which includes a mixture of Likert scales and free text questions. The results of the feedback was as follows: 100% of trainees felt the course met their learning needs and the content was appropriate for their level of training 100% of participants evaluated the course would change their clinical practice with nearly 60% saying it would alter their practice a great deal. The free text comments were overwhelmingly positive with participants liking the range of scenarios, particularly the stressful situations like resuscitation, cardiac arrest and sudden infant death syndrome (SIDS). Confidence and clinical knowledge of trainees improved. Discussions, conclusions recommendations: Return to work is an anxious time for trainees. Organisations need to have a clear programme in place to facilitate the return to training. Our course highlights that simulation can be used successfully to aid trainees to return to work. The results show that the confidence and skills of trainees improved prior to returning to work. Returning candidates clearly have felt proven benefit, attending multiple courses. Using our programme, our recommendation is that simulation can be adapted to other specialities to ensure safe return to work nationally. References: Brightwell A, Minson S, Ward A, Fertleman C. Returning to clinical training after maternity leave. BMJ Careers . 2013; 09.10 Thompson L, Kirk N, McCay N. G340(P) The use of simulation to support out of programme paediatric trainees. Archives of Disease in Childhood 2017;102:A133-A134.